THE EXPRESSION OF LEARNING ORIENTED ASSESSMENT CULTURE: A QUALITATIVE STUDY OF TEACHERS’ PERCEPTIONS ABOUT ASSESSMENT - Raudiene, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article presents the results of a thematic analysis conducted after informal interviews with 10 teachers and a head teacher of one secondary school in the city of Vilnius about their classroom assessment practices. Part of a larger critical ethnographic research exploring the change of school culture when introducing assessment innovation, this analysis reveals common classroom assessment practices, teachers’ beliefs about the role of assessment, and the anxiety the school community shares around standardized testing and examinations. Literature suggests that both formative and summative assessment practices have great potential for improving students’ learning. Teachers are encouraged to integrate assessment into their teaching in order to identify where their pupils are in their learning and the steps they need to take for improvement and progress (Gardner, Hayward, Harlen & Stobart, 2008). However convincing the arguments in favour of change are, the external school evaluation data shows that the real change in the way teachers assess students’ progress is very slow and hardly noticed. The concept of learning oriented assessment culture (Birenbaum, 2014) could provide more understanding about the nature of good classroom assessment and necessary conditions that help to sustain school efforts in improving assessment practices.